The Effect of Work-Family Conflict on Employee Performance Through Job Satisfaction in Female Workers of Cigarettes Factory in Jombang - Henry Dwi Hatmoko; Rizky Febriani; Siti Nurhasanah (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2022)
This study aims to determine the effect of work-family conflict on performance through job satisfaction as a mediating variable on female workers at Tentrem Jaya Lestari Jaya Cigarette Factory Jombang. The study was conducted on production workers with a sample of 125 respondents. Collecting data using questionnaires and variable descriptions to determine respondents' perceptions of the variables. The instrument test in this study uses validity and reliability tests, then the data analysis technique is Partial Least Square (PLS) analysis using the WarpPLS 7.0 application. The results of the variable description show that the work-family conflict experienced is very low, and the performance and job satisfaction are quite high. It is known that the work-family conflict has a significant effect on performance through job satisfaction for the workers of the Sehat Tentrem Jaya Lestari Cigarettes Factory Jombang.